2022
DOI: 10.1007/s12525-022-00599-z
|View full text |Cite
|
Sign up to set email alerts
|

Explainable product backorder prediction exploiting CNN: Introducing explainable models in businesses

Abstract: Due to expected positive impacts on business, the application of artificial intelligence has been widely increased. The decision-making procedures of those models are often complex and not easily understandable to the company’s stakeholders, i.e. the people having to follow up on recommendations or try to understand automated decisions of a system. This opaqueness and black-box nature might hinder adoption, as users struggle to make sense and trust the predictions of AI models. Recent research on eXplainable A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…[15], [23], [27], [62] y [63]. La inteligencia artificial implementada en la robótica y otras tecnologías con un alto grado de autonomía deben ser reguladas y respaldadas por seguridad para la confianza del individuo y posible cliente de las empresas dotadas de IA.…”
Section: Gemelos Digitales (Toma De Decisiones)unclassified
“…[15], [23], [27], [62] y [63]. La inteligencia artificial implementada en la robótica y otras tecnologías con un alto grado de autonomía deben ser reguladas y respaldadas por seguridad para la confianza del individuo y posible cliente de las empresas dotadas de IA.…”
Section: Gemelos Digitales (Toma De Decisiones)unclassified
“…In the first paper, "Explainable product backorder prediction exploiting CNN: Introducing explainable models in businesses", the authors Md Shajalal, Alexander Boden and Gunnar Stevens (Shajalal et al, 2022) explore how intelligent predictive models could be made explainable to the stakeholders in strategic inventory management. It proposes a new convolutional neural network (CNN)-based explainable predictive model for product backorder prediction.…”
Section: Accepted Papersmentioning
confidence: 99%
“…New XAI methods were proposed, such as a novel global XAI approach by means of linguistic rules based on NLP building block (Binder et al, 2022), while Zacharias et al (2022) suggested an innovation regarding the pre-processing stage of AI by a new feature selection method based on XAI. Regarding the impact of XAI, it has been shown that transparent AI can be a very effective tool for decision support in different business domains such as inventory management (Shajalal et al, 2022) or human resources (Hofeditz et al, 2022), and others. For instance, the latter study highlighted that with XAI, bias and discrimination in decision making can be mitigated.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%